2007
DOI: 10.1108/02635570710734244
|View full text |Cite
|
Sign up to set email alerts
|

Intrapreneurship: a comparative structural equation modeling study

Abstract: Purpose -The purpose of this paper is to illustrate the intrapreneurship construct with its predictors and consequences via a model. Previous studies in intrapreneurship have been predominantly concerned with patterns of relationships (coefficients of the model) as opposed to the level of intrapreneurship and other constructs (latent means) in the intrapreneurship model. This study aims to examine both the patterns of relationships and the levels (means) across two countries (the USA and Slovenia) by testing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
1
33

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(204 citation statements)
references
References 57 publications
4
162
1
33
Order By: Relevance
“…In the similar manner, the emerging awareness on intrapreneurship concept has unveilled the neccessity of entrepreneurship among individual in the organisation as entrepreneurship conventionally related to the entrepreneurs or business owners (Antoncic, 2007). Consistent with Schumpeter's (Schumpeter, 1949) view, entrepreneur is the agent of change that stimulate the destruction economy by introducing new market through novel breakthrough thus upsetting the conventional ways of doing things.…”
Section: Introductionmentioning
confidence: 62%
“…In the similar manner, the emerging awareness on intrapreneurship concept has unveilled the neccessity of entrepreneurship among individual in the organisation as entrepreneurship conventionally related to the entrepreneurs or business owners (Antoncic, 2007). Consistent with Schumpeter's (Schumpeter, 1949) view, entrepreneur is the agent of change that stimulate the destruction economy by introducing new market through novel breakthrough thus upsetting the conventional ways of doing things.…”
Section: Introductionmentioning
confidence: 62%
“…Firms that show entrepreneurial behaviour have greater profitability and growth than those that do not adopt entrepreneurial systems (Antoncic, 2007). For this scenario to be true, it is fundamental that managers and all collaborators in a firm modify their attitudes and adopt the characteristics of collaborative entrepreneurship (Wunderer, 2001).…”
Section: Alliances As Collaborative Entrepreneurshipmentioning
confidence: 99%
“…In this context, Middel (2008) concluded that entrepreneurial capability is an important requisite for a firm to collaborate effectively with external partners and therefore be able to absorb the beneficial competences of other firms, increasing its level of knowledge and improving its innovative characteristics. According to Antoncic (2007), firms are considered entrepreneurial if they form interfirm relationships and show themselves to be innovative, pro-active and with a capacity for constant selfrenewal. As noted by Gundry and Kickul (2007), entrepreneurship tends to require cooperation and collaboration among many parties.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, companies need to innovate constantly if they want to succeed (Huse et al, 2005;Antoncic, 2007); they need to improve their flexibility, competitiveness, and reactivity (Littunen & Virtanen, 2006). There is a growing consensus that established companies need to nurture 1 Corresponding autor.…”
Section: Introductionmentioning
confidence: 99%